Prenatal glucocorticoid administration enhances bilirubin metabolic capacity and increases Ugt1a and Abcc2 gene expression via glucocorticoid receptor and PXR in rat fetal liver. Issue 7 (20th April 2022) - Kobayashi, Tsukasa; Takeba, Yuko; Ohta, Yuki; Ootaki, Masanori; Kida, Keisuke; Watanabe, Minoru; Iiri, Taroh; Matsumoto, Naoki
Abstract: Aim: Jaundice is especially common in premature infant born before 35 weeks. Because the premature infant liver is not fully developed at birth it may be incomplete the bilirubin metabolism. The purpose was to evaluate the metabolism and the excretion of bilirubin in the premature infant rat liver following prenatal glucocorticoid (GC) administration. Methods: Dexamethasone (DEX) was administered subcutaneously to pregnant Wistar rats for two consecutive days on gestational days 17 and 19. The fetus were delivered by cesarean section in gestational days 19 and 21. The mRNA levels and protein levels of bilirubin‐metabolic enzymes and transporters in the fetal liver tissues were analyzed using RT‐PCR immunohistochemistry staining and ELISA, respectively. We evaluated that the effect of bilirubin‐metabolic enzymes in the primary fetal rat hepatocytes treated with DEX after pretreated with glucocorticoid receptor (GR, Nr3c1) and Pxr (Nr1i2) siRNA. Results: Ugt1a1 and Bsep ( Abcb11 ) mRNA levels were significantly increased in the fetuses by prenatal GC administration. The mRNA levels of nuclear transcription factors Nr1i2, Car ( Nr1i3 ), and Rxrα ( Nr2b1 ) were also significantly increased in the fetuses by prenatal GC administration. In addition, DEX increased Nr1i2, Ugt1a1, and Abcc2 ( Mrp2 ) mRNA levels in the primary fetal hepatocytes. The Nr3c1 or Nr1i2 siRNA‐mediated knockdown suppressed the increases of Ugt1a1, and Abcc2 mRNA levels induced by DEX, indicating that DEX are mediated by GC receptor and PXR in primary fetal hepatocytes. Conclusions: These results suggest that prenatal GC administration increases bilirubin‐metabolic ability, in the premature liver, which may prevent jaundice in neonates.